Management of Intra Uterine Growth Restriction with Month wise Ksheera Kashaya (International Journal of Ayurveda and Pharma Research, 2023)
Intrauterine Growth Restriction (IUGR) is a main health condition affecting pregnant women and its outcomes are perinatal mortality and morbidity. In the prevailing case a 38 year-old Multi gravida who undergone regular ante natal check-up was detected with Intrauterine Growth restriction at 21 weeks of gestation. The estimated weight of the foetus was found less than 19 percentile and there has been oligohydramnios, pleural effusion and increased pericardial fluid to the foetus on additional evaluation. She was given allopathic control initially; however, the circumstance remains unchanged. She turned into Ayurveda and was handled with the treatment principles of Garbhasosha (foetal emaciation). She was managed by month wise medicated Ksheera kashaya (milk decoction) for Brimhana (nourishing) and pacifying Vata. She delivered a full term healthy female baby of weight 2.57kg through a Lower Segment Caesarean Section. The prognosis by the allopathic system was poor in this case and there are no interventions in their system to improve placental perfusion. In this case the condition was achieved through month wise treatment and specification of Ayurvedic formulations. Completed in a brief span of time, thereby stopping the want for early delivery and the persisted until 39 weeks of gestation. Being a term delivery, the need for neonatal extensive care was no longer arising. The cutting-edge method shows that Ayurveda is tremendously powerful in intra uterine growth restriction and its complications. This case opens the scope for additional studies within the region of Intrauterine Growth Restriction with Ayurvedic drug treatments.